Data Journalism as a Service: Digital Native Data Journalism Expertise and Product Development - Appelgren, Ester (2020)
The combined set of skills needed for producing data journalism (e.g., investigative journalism methods, programming, knowledge in statistics, data management, statistical reporting, and design) challenges the understanding of what competences a journalist needs and the boundaries for the tasks journalists perform. Scholars denote external actors with these types of knowledge as interlopers or actors at the periphery of journalism. In this study, we follow two Swedish digital native data journalism start-ups operating in the Nordics from when they were founded in 2012 to 2019. Although the start-ups have been successful in news journalism over the years and acted as drivers for change in Nordic news innovation, they also have a presence in sectors other than journalism. This qualitative case study, which is based on interviews over time with the start-up founders and a qualitative analysis of blog posts written by the employees at the two start-ups, tells a story of journalists working at the periphery of legacy media, at least temporarily forced to leave journalism behind yet successfully using journalistic thinking outside of journalistic contexts.